PENGARUH MODEL PEMBELAJARAN PROBLEM BASED INTRUCTION (PBI) BERBANTUAN VIDEO TERHADAP HASIL BELAJAR DASAR TEKNIK PENGELASAN DAN FABRIKASI LOGAM SISWA KELAS X JURUSAN TEKNIK PENGELASAN SMK NEGERI 1 GUGUK - Bagus Ramadani; Ambiyar Ambiyar; Junil Adri; Sri Rizki Primandari (Unversitas Negeri Padang, 2024)
Sustaining and enhancing the quality of education presents a significant challenge. Many education systems face problems such as inappropriate curricula, lack of qualified teachers, and inadequate teaching methods. This study aims to determine the significance of PBI learning materials by video assistance. The subjects of this research were 70 people from SMK Negeri 1 Guguk. Quasi-experimental design, test-sheet research tools, validity, reliability, normalcy, homogeneity, and independent t-tests are the research methods employed. In this study, the experimental class achieved a post-test score of 76.89, compared to 64.49 for the control class. This proves that the treatment given by PBI learning has an impact on academic performance of student in the experimental group were contrasted with those in the group under supervision, who were not given any intervention. As for the outcomes of the normality test wich was carried out, the data obtained a normal distribution value of sig> 0.05, the results of the homogeneity test obtained post-test data greater than (sig>0.05), the variance was homogeneous, and the independent t-test results were obtained at 6.674. then the T Test result is 0.00 in accordance by the provisions of the sig value (2-tailed) <0.05). Consequently, it was determined that the cognitive aspects of students regarding the impact Considering the use of the PBI learning model with video assistance on the learning results of Basic Welding and Metal Fabrication Techniques for Class study control class 64.49 and experimental class 76.89.